2018
DOI: 10.1038/s41398-018-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant salience network functional connectivity in auditory verbal hallucinations: a first episode psychosis sample

Abstract: Auditory verbal hallucinations (AVH) often lead to distress and functional disability, and are frequently associated with psychotic illness. Previously both state and trait magnetic resonance imaging (MRI) studies of AVH have identified activity in brain regions involving auditory processing, language, memory and areas of default mode network (DMN) and salience network (SN). Current evidence is clouded by research mainly in participants on long-term medication, with chronic illness and by choice of seed region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 59 publications
7
57
1
Order By: Relevance
“…In this study, we did not find a significant correlation between gFCD and the AVH severity in BPD-AVH patients. This observation was in agreement with previous findings that alterations in brain function were not correlated with the severity of clinical symptoms, for which it has been postulated that these brain alterations could be related to the trait of the symptoms rather than the "state" of symptoms [48][49][50][51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we did not find a significant correlation between gFCD and the AVH severity in BPD-AVH patients. This observation was in agreement with previous findings that alterations in brain function were not correlated with the severity of clinical symptoms, for which it has been postulated that these brain alterations could be related to the trait of the symptoms rather than the "state" of symptoms [48][49][50][51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 93%
“…The question of how the anterior hippocampus functionally interacts with the salience network in FEP is of interest given aberrant salience monitoring is a core feature of psychosis, and the anterior hippocampus plays a key role in salience attribution: in humans, it activates in response to mismatch or novelty, 43,44 co-activates with the anterior insula during threat appraisal, 45 and has strong FC with subcortical nodes involved in salience processing 22,46,47 ; in rodents, the ventral hippocampus modulates salience according to context via interactions with the amygdala and prefrontal cortical areas. 45,48,49 Although the salience network and isolated nodes (dACC and insular cortex) have been previously reported to show altered within network FC (typically hypoconnectivity) relative to controls in UHR, 50,51 antipsychotic naïve FEP, 52,53 and chronic medicated schizophrenia patients, [54][55][56][57][58] few studies have assessed hippocampal FC with this network. Current findings suggest relative hypoconnectivity between the anterior hippocampus and cortical hubs in the salience network in unmedicated FEP patients.…”
Section: Fep-control Differences In Anterior Hippocampal-brain Fcmentioning
confidence: 99%
“…Gyral and sulcal architecture is intrinsically related to the brain’s functional organization 14 . Functional neuroimaging studies have consistently reported alterations in the brain’s resting state networks in people who experience hallucinations, particularly in the salience network, which engages the anterior cingulate and anterior insula to determine the origin and salience of internal and external stimuli 15 , 16 . The salience network equally coordinates the transition between functional networks related to self- and task-processing, suggesting cross-network abnormalities in the manifestation of hallucinations 17 .…”
Section: Introductionmentioning
confidence: 99%